2010
DOI: 10.1007/s10404-010-0698-9
|View full text |Cite
|
Sign up to set email alerts
|

Laser microstructuration of three-dimensional enzyme reactors in microfluidic channels

Abstract: International audienceIn this paper, we report on the fabrication of three-dimensional (3D) enzymatic microreactors within polydimethylsiloxane microfluidic channels through a photocrosslinking mechanism mediated by the two-photon absorption process at the focal point of pulse lasers, i.e., a sub-nanosecond Nd:YAG microlaser or a femtosecond Ti:Sapphire laser. This approach allows the building of localized 3D trypsin structures with submicron resolution. The fabrication of two different trypsin structures was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 26 publications
(28 reference statements)
0
32
0
Order By: Relevance
“…Kaehr et al showed that binding fluorescence is proportional to the protein concentration 56 , implying not only retained function but also a non-preferential process. There have also been some reports about the retention of protein enzymatic functions 35,36,38 . However, to date there have been no analyses of protein activity or quantitative assessments of active units.…”
Section: Retention Of Protein Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kaehr et al showed that binding fluorescence is proportional to the protein concentration 56 , implying not only retained function but also a non-preferential process. There have also been some reports about the retention of protein enzymatic functions 35,36,38 . However, to date there have been no analyses of protein activity or quantitative assessments of active units.…”
Section: Retention Of Protein Functionmentioning
confidence: 99%
“…The non-invasive nature of forming crosslinked proteins in solution enables the fabrication of various complex embedded 3D structures. These structures can be nested on the substrate surfaces 33,34 or embedded into transparent devices such as microfluidic channels [35][36][37] . In addition to 3D fabrication and superior resolution, another advantage of the multi-photon cross-linking of proteins as 3D printing materials is the potential to retain the protein functions after fabrication 35,38,39 .…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, the extraordinary ability of 2PP to polymerize and structure 3D objects within a closed microchannel system was reported for use as in-chip filters or as in-chip enzymatic reactors. 26,27 Here, we demonstrate the fabrication of reproducible 3D structures with cell-sized pores by 2PP inside the closed channel of a commercially available disposable polymer microfluidic chip (Fig. 1) designed for chemotaxis analysis in non-structured hydrogel materials.…”
Section: Introductionmentioning
confidence: 97%
“…This ensures a good fit and reduces the amount of chemicals required. In-chip DLW was first used for enzymatic 3-D microreactors by Iosin et al 26 Amato et al 16 fabricated a porous filter into an existing microchannel and Serra et al…”
Section: Introductionmentioning
confidence: 99%